Physical activity participation among children diagnosed with mental health disorders: A qualitative analysis of children's and their guardian's perspectives. Issue 5 (3rd September 2022) - Fortnum, K.; Reid, S.; Elliott, C.; Furzer, B.; Wong, J.; Jackson, B.
ABSTRACT: Purpose: Children with mental health disorders have lower physical activity levels compared to their peers; however, minimal research has been conducted to date to understand their unique experiences of physical activity. We sought to better understand these experiences, along with contributing factors, through interviews with children with mental health disorders and their parents/guardians. Methods: Semi-structured interviews were conducted with 20 children (6–12 years, 17 males) and 18 parents/guardians from a metropolitan mental health service, and data were analysed using a thematic analysis approach. Results and conclusions: Children predominantly participated in play-based, unstructured physical activities with their families. Aspects of social connection (or disconnection), children's movement skill and resilience, and a desire to experience success and enjoyment, were described as influencers of children's physical activity participation experiences (and levels). Children and parents/guardians also emphasised the importance of emotional and physical support surrounding physical activity participation, and the need for suitably tailored programmes and environments. Recommendations are offered to facilitate physical activity programming that meets the specific needs of children with mental health disorders and their families.